Metaphorical Conceptualization Employed by Animal Lexicon "Dog" in English and Indonesian Proverbs: a Comparative Study - Nitis Asmara Bachrun; Suhandano Suhandano (Journal of Social Research, 2023)
The proverb is a cultural item, embodied in a form of figurative expression, being handed over generations within a particular speech community. Proverbs carry out certain information regarding the culture of the speech community, such as the lifestyles, values, and perspectives of the society. Animal lexicon "dog" becomes the most frequently appeared animal lexicon within proverbs in English and Indonesian languages. There are 3 major types of concepts being carried out by the lexicon "dog" within the proverbs investigated in this research, which are the positive human traits, the negative human traits, and situational phenomena. Meanwhile, there are a total of 20 concepts found to be the target domains of the lexicon "dog" within the proverbs being examined in this research, which are as follows: 1) despicable person, 2) opportune aptitude, 3) the spiteful one, 4) greedy soul, 5) significant problems, 6) being cornered, 7) an iniquity, 8) companion faithfulness, 9) futile individual, 10) menace aptitude, 11) fortunate aptitude, 12) the ungrateful one, 13) the powerful one, 14) insincerity, 15) brave soul, 16) humble background, 17) decisions significance, 18) perceived aspects, 19) the grateful one, 20) coward. The speech community of the English language has distinctive points from the speech community of the Indonesian language in their way to metaphorically conceptualizing the lexicon “dog”. However, there are still typical concepts that appeared as the target domains of the lexicon “dog” preserved by both of the speech communities.